Five cases of short stature and delayed puberty with primary empty sella syndrome - Atiqur Rahman, Mohammad; Morshed, Md Shahed; Jahan, Sharmin; Hasan, Mashfiqul; Hasanat, Muhammad Abul; Fariduddin, Md (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
We reported five adolescent boys of proportionate short stature and delayed puberty. None of the patients had any risk factors or stigma of growth hormone and other pituitary hormone deficiency. But investigations revealed panhypopituitarism with empty sella detected by pituitary MRI in all cases. Children with primary empty sella syndrome require an active evaluation of hormonal status for long-term outcomes. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2022; 1 (2): 69-71